2020
DOI: 10.1002/smll.202006287
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Early Healing Phase with Titania Nanotube Arrays on Tunable Diameters to Accelerate Bone Regeneration and Osseointegration

Abstract: enlarges postoperative complications and morbidity. [1] Implantable materials with the desired surface to stimulate bone formation and prevent prosthesis implant loosening within the host bone remain as unsolved and intractable issues. [2] Manipulating a rapid, stable, and permanent bond between the implant and host bone upon the interface is pivotal for the maintenance of the enduring implant function and integrity. Miscellaneous sophisticated designed implantable materials confer favorable integrity to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…Titanium dioxide (TiO ) nanotube arrays constitute a highly adjustable material that is used for various applications. Recent advances in the development of devices for solar energy conversion [ 1 ], photocatalysis [ 2 ], biomedicine [ 3 ] and biosensors [ 4 , 5 ] have been achieved by specifically modifying the starting material: titania nanotube arrays. These arrays comprise general characteristics of bulk TiO that are enhanced by the enormous surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO ) nanotube arrays constitute a highly adjustable material that is used for various applications. Recent advances in the development of devices for solar energy conversion [ 1 ], photocatalysis [ 2 ], biomedicine [ 3 ] and biosensors [ 4 , 5 ] have been achieved by specifically modifying the starting material: titania nanotube arrays. These arrays comprise general characteristics of bulk TiO that are enhanced by the enormous surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous works demonstrated that various diameter TiO 2 NT structures can also induce the anti-inflammatory response of hosts (Chamberlain et al [21], Smith et al [189], Neacsu et al [20], Yao et al [190], Bai et al [191]). The surface modification induced by the nanotube structures combined with annealing can change the hemocompatibility of TiO 2 NTs, by alleviating platelet activation (Mazare et al [111,150], Junkar et al [15], Huang et al [192], Gong et al [193], Bai et al [191,194]).…”
Section: Tailoring Osteoinduction With Anodicmentioning
confidence: 99%
“…Many previous works demonstrated that various diameter TiO 2 NT structures can also induce the anti-inflammatory response of hosts (Chamberlain et al [21], Smith et al [189], Neacsu et al [20], Yao et al [190], Bai et al [191]). The surface modification induced by the nanotube structures combined with annealing can change the hemocompatibility of TiO 2 NTs, by alleviating platelet activation (Mazare et al [111,150], Junkar et al [15], Huang et al [192], Gong et al [193], Bai et al [191,194]). Several in vivo studies have shown that TiO 2 nanotubular layers could induce successful peri-implant bone formation/osseointegration in various animal models using different diameter NTs: von Wilmowsky et al (30 nm diameter nanotubes) [195], Wang et al (30,70, and 100 nm diameter NTs) in minipigs [174], Alves-Rezende et al (≈ 74 nm diameter NTs) [196], Baker et al (TiO 2 NTs-in vitro and in vivo intramedullary fixation) in rats [197], or the review of Wang et al [198] for the effect of TiO 2 NTs grown on the implants' surface on osseointegration in animal models.…”
Section: Tailoring Osteoinduction With Anodicmentioning
confidence: 99%
“…For example, Yao et al prepared nanoflake structures through hydrothermal treatment of Ti, and demonstrated that the nanostructure has superior osteogenesis [ 29 ]. Bai et al studied the influence of the nanosurface characteristic on the blood clot property and inflammatory reaction in bone regeneration, and concluded that a titania nanotube with a diameter of 15 nm facilitates bone regeneration by manipulating a favorable osteoimmunomodulatory environment [ 30 ].…”
Section: Introductionmentioning
confidence: 99%